Civil Responsibility Model of Coastal State to Oil Pollution in the Sea as the Impact from the Stipulation of Dumping Area by Tanker Ship - Purwendah, Elly Kristiani; Djatmiko, Agoes; Pudyastiwi, Elisabeth (Faculty of Law Universitas Negeri Semarang, 2019)
The research findings reveal a pluralistic understanding of dumping within the Indonesian Legal System, evident in various laws, including Law No. 17 of 1985 on the Ratification of UNCLOS, Law No. 32 of 2009 on Environmental Protection and Management, Government Regulation No. 29 of 2014 on the Prevention of Environmental Pollution, Ministerial Regulation No. 136 of 2015 on the Second Amendment to Ministerial Regulation No. 52 of 2011 on Dredging and Reclamation, and Ministerial Decree No. 4 of 2005 on the Prevention of Pollution from Ships. Dumping countermeasures are primarily perceived as acts related to dredging and reclamation, identified as contributors to the silting of shipping channels. Notably, Indonesia has not ratified the London Dumping Convention, and there is a lack of a definitive list specifying wastes requiring special arrangements and absolute prohibition within the coastal states' territories. Consequently, compensation has not been prioritized as a state-led measure for marine environmental protection. The state's responsibility, enforced through the State Attorney, necessitates procedural formalities, including a special power of attorney. Collaborative efforts with relevant institutions, particularly the Ministry of Environment and Forestry, are deemed essential. The current landscape in Indonesia reveals overlapping authorities among agencies, leading to conflicting interpretations of civil lawsuit issues related to environmental damages. The proposed model advocates for centralizing environmental priorities within the Ministry of Environment and Forestry, coordinated through the State Attorney, as a strategic step towards addressing these complex issues.